Two-electron capture cross sections into ground state in collision of bare projectile ions with helium atom - Ghosh, S. (Array, 2009)
Double charge-transfer cross-sections from ground state of helium atoms by multiply-charged bare ions have been studied in the energy range 50 - 200 keV/amu to investigate the dependence of cross-sections on the charge state of different ions (He2+, Li3+, Be4+, B5+, C6+, N7+ and O8+). In our calculation, we have employed the four-body boundary-corrected continuum intermediate state (BCCIS-4B) approximation. The variation of double charge transfer cross sections of bare ions into the ground state is displayed versus the incident projectile energy. Due to the non-availability of any theoretical and experimental findings in that energy range for collision systems under study (Be4+, B5+, C6+, N7+ and O8+ + He), we can not compare the present results with other data. We have also analysed differential double-capture cross sections for the collision of a-particle with helium atom at 1500 keV. The obtained results for the differential double-capture cross sections into the ground state are compared with the experimental data and a satisfactory agreement has been obtained